Determination of some physical properties of Agave tequilana Weber for mechanizing crop - Saldaña Robles Alberto; Serwatowski Hlawinska, Ryszard Jerzy; Saldaña Robles Noé; Gutiérrez Vaca César; Cabrera Sixto José Manuel; García Barrón Salvador (Revista Mexicana de Ciencias Agrícolas, 2018)
In this study some physical properties (dimensions and weights) of Agave tequilana Weber plant were determined and of their individual elements (pineapple, leaves and root) using basic measuring devices, as well it was measured unitary energy required for leaves cut. These parameters would be used in the design of agave’s harvester-shredder. The study was made at “El Copal”, municipality of Irapuato, Guanajuato, Mexico. To quantify unitary energy two parameters were assessed. The firs parameter was energy used during agave leaf cut this energy was assessed in 10 positions along 1m length leaf, making four repetitions. A device which applies free falling was used. The second parameter was transversal section area, in the same positions were cut energy where made in leaf, using artificial vision. From this information unitary energy was calculated, giving as result an average of 2.5 J·cm-2. The physical properties assessed have high variability. Mean of these results coincides with the values obtained by other authors. It was found that there is well defined relation between: cut energy, leaf transversal section area and position along leaf, in the extent that one of the variables increases the other increases according to second order polynomial.